Experimental study of acid‐sulfate alteration of basalt and implications for sulfate deposits on Mars. Issue 4 (8th April 2013) - McCollom, Thomas M.; Robbins, Mark; Moskowitz, Bruce; Berquó, Thelma S.; Jöns, Niels; Hynek, Brian M.
Abstract : [1] Acid‐sulfate alteration of basalt by SO2 ‐bearing volcanic vapors has been proposed as one possible origin for sulfate‐rich deposits on Mars. To better define mineralogical signatures of acid‐sulfate alteration, laboratory experiments were performed to investigate alteration pathways and geochemical processes during reaction of basalt with sulfuric acid. Pyroclastic cinders composed of phenocrysts including plagioclase, olivine, and augite embedded in glass were reacted with sulfuric acid at 145 °C for up to 137 days at a range of fluid : rock ratios. During the experiments, the phenocrysts reacted rapidly to form secondary products, while the glass was unreactive. Major products included amorphous silica, anhydrite, and Fe‐rich natroalunite, along with minor iron oxides/oxyhydroxides (probably hematite) and trace levels of other sulfates. At the lowest fluid : rock ratio, hexahydrite and an unidentified Fe‐silicate phase also occurred as major products. Reaction‐path models indicated that formation of the products required both slow dissolution of glass and kinetic inhibitions to precipitation of a number of minerals including phyllosilicates and other aluminosilicates as well as Al‐ and Fe‐oxides/oxyhydroxides. Similar models performed for Martian basalt compositions predict that the initial stages of acid‐sulfate alteration of pyroclastic deposits on Mars should result in formation of amorphous silica, anhydrite, Fe‐bearing natroalunite, and kieserite, along with relict basaltic glass. In addition, analysis of the experimental products indicates that Fe‐bearing natroalunite produces a Mössbauer spectrum closely resembling that of jarosite, suggesting that it should be considered an alternative to the component in sulfate‐rich bedrocks at Meridiani Planum that has previously been identified as jarosite. Key Points: Alteration of basalt dominated by amorphous SiO2, anhydrite, and natroalunite Kinetic inhibitions to dissolution/precipitation of specific phases identified Acid alteration on Mars produces silica, anhydrite, natroalunite, and kieserite